Pelatihan Penerapan Pembelajaran Aktif berorientasi Higher Order Thinking Skill: Pemberdayaan Guru SD selama Pandemi Covid-19 - Afib Rulyansah; Rizqi Putri Nourma Budiarti; Emy Yunita Rahma Pratiwi (Utan Kayu Publishing, 2022)
Students are dissatisfied with online education after the Covid-19 epidemic. Students, especially in this digital era, need to develop higher order thinking skills in their academic activities. Although most teachers still do not have strong knowledge about HOTS-based active learning, the value of the teaching process carried out by teachers is not yet very capable of measuring high-level thinking skills, especially in Tiris Regency. For primary school educators in Tiris District, this program will help them improve the quality of HOTS-based teaching. Elementary school teachers from Tiris Regency took part in this program. This six-month program includes a combination of classroom instruction, hands-on workshops, and one-on-one tutoring. The teacher's ability to apply HOTS-based active learning has increased as a result of the boot camp that has been given. Abstrak: Siswa tidak puas dengan pendidikan online setelah epidemi Covid-19. Siswa, khususnya di era digital ini, membutuhkan pengembangan kemampuan berpikir tingkat tinggi dalam kegiatan akademik mereka. Meskipun sebagian besar pengajar masih belum memiliki pengetahuan yang kuat tentang pembelajaran aktif berbasis HOTS, nilai proses pengajaran yang dilakukan oleh guru belum terlalu mampu dalam melakukan pengukuran kemampuan berpikir lelvel tinggi, khususnya di Kabupaten Tiris. Bagi para pendidik sekolah dasar di Kabupaten Tiris, program ini akan membantu mereka meningkatkan kualitas pengajaran berbasis HOTS. Guru SD dari Kabupaten Tiris ikut ambil bagian dalam program ini. Program enam bulan ini mencakup kombinasi instruksi kelas, lokakarya langsung, dan bimbingan satu lawan satu. Kemampuan guru dalam menerapkan pembelajaran aktif berbasis HOTS meningkat sebagai hasil dari boot camp yang telah diberikan.